The Effect of Crumb Rubber as a Substitute for Fine Aggregate in Lightweight Concrete with Addition of Fly Ash - Fuad, Indra Syahrul; Firda, Ani (JURUSAN TEKNIK SIPIL, 2024)
In the construction industry, concrete is an important component and is frequently utilized as a building material. Coarse and fine aggregate make up the majority of the content in concrete. Although some earlier researchers have replaced aggregate in concrete, advancements in industry and time have made it possible to replace aggregate with waste as well. The impact of substituting fine aggregate in a concrete mixture with a quality of 20 MPa with 25% and 50% crumb rubber is investigated in this study. Concrete's compressive strength was tested using cylindrical specimens that were aged 3, 7, 14, 21, and 28 days, while its flexural strength was tested using specimens in the shape of beams that were aged 28 days. The concrete compressive strength test reduced by 58.85% at a 25% crumb rubber content and by 78.73% at a 50% crumb rubber content, according to the test findings. Concrete's flexural strength, on the other hand, decreased by 23.66% and 49.23% for concrete with a 50% crumb rubber content and 25% crumb rubber content, respectively. This means that crumb rubber can be used in concrete mixtures for non-structural purposes. <w:LsdException Locked=